Monitoring of chlorine concentration in drinking water distribution systems using an interval estimator - Łangowski, Rafał; Brdys, Mietek A. (Zielona Góra: Uniwersytet Zielonogórski)
This paper describes the design of an interval observer for the estimation of unmeasured quality state variables in drinking water distribution systems. The estimator utilizes a set bounded model of uncertainty to produce robust interval bounds on the estimated state variables of the water quality. The bounds are generated by solving two differential equations. Hence the numerical efficiency is sufficient for on-line monitoring of the water quality. The observer is applied to an exemplary water network and its performance is validated by simulations.
Keywords: estimators; bounding methods; modelling dynamics; water quality